2023
DOI: 10.1108/jtf-03-2023-286
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: How COVID-19 changed the world of tourism research

Abstract: Disruption causes significant change, whether for good or bad (Yeoman et al., 2021). COVID-19 has been a catalyst for change and has driven the desire for a better future. It has accelerated our understanding of climate change and been responsible for the word "regenerative tourism". In this issue of the Journal of Tourism Futures, we explore how COVID-19 has changed, accelerated and brought the future to the forefront of research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Many publications have been produced the past three years about the impacts of COVID-19 on the tourism and hospitality sector and whether this is a game changer or not (Cheer et al, 2021;Lew (Information about the authors can be found at the end of this article.) Papp et al, 2023;Tomassini et al, 2021;Yeoman, 2023). Given that the COVID pandemic is quite a recent phenomenon affecting tourism, most of these papers remain conceptual show scenarios, visions and potential outlooks.…”
Section: Introductionmentioning
confidence: 99%
“…Many publications have been produced the past three years about the impacts of COVID-19 on the tourism and hospitality sector and whether this is a game changer or not (Cheer et al, 2021;Lew (Information about the authors can be found at the end of this article.) Papp et al, 2023;Tomassini et al, 2021;Yeoman, 2023). Given that the COVID pandemic is quite a recent phenomenon affecting tourism, most of these papers remain conceptual show scenarios, visions and potential outlooks.…”
Section: Introductionmentioning
confidence: 99%